PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP DI SMP NEGERI 2 LUBUK BASUNG - Afriani, Nola; Lestari, Tuti; Oktafrida, Leni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Understanding the concept of science becomes a very important skill for students to possess, as it is essential for building basic scientific concepts that are applied in everyday life. The purpose of this research is to determine the improvement in concept understanding of class VIIIA students at SMP Negeri 2 Lubuk Basung for the 2024/2025 academic year and to describe the improvement in concept understanding on the excretory system material through the application of the Problem Based Learning (PBL) model using Canva media. The type of research is classroom action research conducted in two cycles. The research sample is class VIIIA with a total of 32 students. The research results show the successful implementation of learning, marked by teacher activity with a score of 80.4% and student activity with a score of 71.1%. Based on the data from the concept understanding test of class VIIIA students in cycle I with an average score of 56.7, while in cycle II the average score of students was 80.3. The results indicate that once the Problem Based Learning approach was implemented in class VIIIA at SMP Negeri 2 Lubuk Basung, students' conceptual comprehension improved.